2020
DOI: 10.1108/gm-09-2019-0162
|View full text |Cite
|
Sign up to set email alerts
|

Gender makes the difference: the moderating role of gender on the relationship between management structure and performance in banking

Abstract: Purpose This study aims to explore the factors moderating possibly indirect relationships between gender diversity and its effect on bank performance. The causality of this relationship remains unclear. Design/methodology/approach The sample consists of all banks (n = 27) operating in Serbia. Findings The gender diversity-performance relationship is indirect. The gender diversity of executive boards positively impacts bank performance, over a threshold level. This is observed only in banks where gender div… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 38 publications
(89 reference statements)
1
17
0
Order By: Relevance
“…It is also argued by Roberts (2015) that banks and accounting firms have sought to devise ways of assessing gender dividends to be gained from investing in women. Gender diversity is not only found to moderate or be moderated by the influence of other economic and demographic variables but also to moderate or mediate itself in the relationship to bank performance (Stefanovic & Barjaktarovic, 2020). These authors found that exploring mediating effects become crucial in contemporary research of gender diversity and performance nexus.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…It is also argued by Roberts (2015) that banks and accounting firms have sought to devise ways of assessing gender dividends to be gained from investing in women. Gender diversity is not only found to moderate or be moderated by the influence of other economic and demographic variables but also to moderate or mediate itself in the relationship to bank performance (Stefanovic & Barjaktarovic, 2020). These authors found that exploring mediating effects become crucial in contemporary research of gender diversity and performance nexus.…”
Section: Introductionmentioning
confidence: 93%
“…Some studies examine whether social responsibility plays a role between the appointment of women to the bank's board of directors and performance, while other studies focus on board diversity indicators as moderators or mediators of board diversity and performance relationships. All these studies find that gender diversity and the real influence of women in making business decisions depend on other factors such as cultural, social responsibility, and socioeconomic (Stefanovic & Barjaktarovic, 2020). Brieger et al (2019) investigated the effect of country-level emancipative forces on corporate gender diversity around the world and explained how action resources, emancipative values and civic entitlements enable, motivate and encourage women to take leadership roles on corporate boards.…”
Section: Introductionmentioning
confidence: 99%
“…Stefanovic and Barjaktarovic (2021) consider these issues further in a study of 27 commercial banks operating in Serbia. Choice of context was influenced by Serbia’s status as first non-EU nation to announce formal measures for gender equality.…”
Section: Serbian Study and Findingsmentioning
confidence: 99%
“…One of the most significant challenges the company faced was tackling the under-representation of female employees in the leadership/ management structure (Stefanovic and Barjaktarovic, 2021). To address this, in 2019 they replaced the existing executive committee of eight senior male managers with seven operational committees that included representatives from across the business.…”
Section: Management Structurementioning
confidence: 99%